2020
DOI: 10.1177/2325967119897881
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective 2-Year Clinical Evaluation of Augmented Hip Abductor Tendon Repair

Abstract: Background: Hip abductor tendon (HAT) tearing is commonly implicated in greater trochanteric pain syndrome. Studies reporting surgical outcomes are often on small cohorts and with limited information on functional improvement. Purpose: To report the 2-year clinical and functional outcomes in a series of patients undergoing HAT repair augmented with a ligament augmentation and reconstruction system (LARS) ligament. Study Design: Case series; Level of evidence, 4. Methods: Between October 2012 and December 2016,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…This is likely due to the fact that gluteus medius tendon tears predominantly occur in tendinopathic tendons and surgical repair is often delayed following tear occurrence [9,24]. While new materials and biologics may enhance such repairs [25], development of these strategies are hampered by the lack of a representative, pre-clinical model which can mimic the loads and stresses following surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the fact that gluteus medius tendon tears predominantly occur in tendinopathic tendons and surgical repair is often delayed following tear occurrence [9,24]. While new materials and biologics may enhance such repairs [25], development of these strategies are hampered by the lack of a representative, pre-clinical model which can mimic the loads and stresses following surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of biological or synthetic tissue augmentation is to decrease retear rates and increase patient satisfaction. Ebert et al 7 reported on a consecutive series of 146 patients who underwent open gluteal tendon repair using synthetic augmentation with the Ligament Augmentation and Reconstruction System. They reported significantly improved clinical and functional outcomes, high levels of patient satisfaction, and a relatively low failure rate up to 24 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gluteus medius and minimus tendon tears have been recognized as a major cause of recalcitrant greater trochanteric pain syndrome. 6,7 Some authors noted the similarity of gluteus medius and minimus tendon insertions on the greater trochanter with those of the rotator cuff, leading to term hip abductor tendon tears as “rotator cuff tears of the hip.” 3,15…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the patients demonstrated significant improvement in pain, gait, strength, and subjective outcomes at a minimum of 2-year follow-up. 23 In patients undergoing abductor tendon suture-anchor repair augmented with a transosseous synthetic scaffold (LARS; Corin Group, Cirencester Cloucestershire, UK), Ebert et al 20,24 reported significant improvement in all mean patient PROs and clinical scores, including hip abductor strength and gait performance in 142 patients.…”
Section: Discussionmentioning
confidence: 99%